COMPONENTS OF PEDAGOGICAL TECHNOLOGY OF FORMATION OF STUDENTS’ PROFESSIONAL AND VALUE ORIENTATION TOWARDS LABOR ACTIVITY - Morin, Oleh (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article deals with the understanding of pedagogical technology that is associated with the search for ways to maximize the results of the educational process through analysis, selection, design and control of all its stages. The properties of algorithms are inherent in pedagogical technologies. They also contain a description of actions, the consistent implementation of which by teachers in similar conditions allows you to achieve similar results. The introduction of pedagogical technology during reproducing the forms, methods and means inherent in it, makes it possible for pedagogical workers to introduce subjectively significant content working with each specific person, to contribute to the formation of students’ readiness for self-study and self-development, to take into account the psychological characteristics of each student. According to the author, this pedagogical technology includes the following components: target (the goal and the guiding principles defined by it), procedural and practical (content, pedagogical tools, forms, methods, as well as the mechanism of the formation process itself), control and evaluation (target diagnostics of intermediate and final results), process control component (description of the organizational structure that provides vocational guidance activities of the subjects of the educational process and the coordination of this activity), effective (definition of the prevailing image-ideal). The introduction of pedagogical technology provides a targeted and systematic influence on the personality in the process of career-oriented educational activities, which takes place in the conditions of scientifically grounded study and consideration of the interests, inclinations, abilities and other individual characteristics of students, as a result, will ensure the formation of their professional and value orientations towards labor activity. As a result, it creates favorable conditions for the personal and professional self-determination of the individual, to ensure his or her preparation for the delivery of a conscious and well-grounded plan for personal implementation in the labor and professional spheres, as well as support in actions aimed at achieving this goal.